Documentary Time : Film and Phenomenology - Wahlberg, Malin (Book collections on Project MUSE., 2008)
Finding the theoretical space where cinema and philosophy meet, Malin Wahlberg's sophisticated approach to the experience of documentary film aligns with attempts to reconsider the premises of existential phenomenology. Wahlberg discusses a corpus of clas.